FATORES QUE INFLUENCIAM AS TAXAS DE PRENHEZ E PERDA GESTACIONAL EM FÊMEAS NELORE SUBMETIDAS À INSEMINAÇÃO ARTIFICIAL EM TEMPO FIXO NO BRASIL - Lucas Gomes da Silva (2023)
Artificial insemination in Brazil has been evolving with an increase in inseminated cows with an expected average pregnancy rate of 50% and for the chain to be productive, it is desirable that the mother delivers one calf per year, with the mother who lost the calf a high cost on the property. However, bovine fertility is a multifactorial process, counting on semen quality, female fertility, management, precise timing, postpartum anestrus and BCS. On the other hand, semen fertility, often neglected, must be considered, due to the great impact it can have on pregnancy rates. On another important point, some studies evaluating pregnancy losses observed great variation in rates and were also influenced by breed, BCS, category, farm, but there are few farms that evaluate and we were able to identify losses only after the first diagnosis of pregnancy, with approximately 30 days. A greater understanding of the factors that influence fertility is essential to improve pregnancy rates and reduce the occurrence of embryonic mortality in beef herds. The objective of the current study was to evaluate retrospective data of pregnancy per artificial insemination (P/AI) and pregnancy loss in Nelore females subjected to timed-AI (TAI) in Brazil. Data from 40,104 TAI collected from six breeding seasons (2016 to 2022) were analyzed, and the effects of animal category (e.g., classification based on age and parity), farm, month of parturition, sire, sire breed (Nelore vs Angus), estrus expression at TAI, animal temperament, and body condition scores (BCS) were evaluated. P/AI and pregnancy loss were affected (P < 0.001) by animal category. There was also an effect of farm (P = 0.0013) on P/AI and pregnancy loss (P = 0.001), as P/AI ranged from 49.28% and 55.58% and pregnancy loss from 3.37% to 6.89% across the herds evaluated. Month of parturition also affected (P < 0.001) P/AI and was higher for cows that became pregnant at the beginning of the previous breeding season. Calmer animals, presenting lower velocity scores while exiting the chute following TAI, achieved higher P/AI (P < 0.001). Lower BCS at TAI was associated (P < 0.001) with increased pregnancy loss, and BCS gain following AI was associated (P < 0.001) with reduced rates of embryonic mortality. There was a major effect (P < 0.001) of sire on P/AI and pregnancy loss, as P/AI ranged from 11 to 79%, and embryonic mortality from 0 to 40% for the bulls used in the study, highlighting the importance of the sire fertility on overall pregnancy success. Results from the current study reinforce the idea that animal category, BCS at the onset of estrous synchronization, BCS gain following AI, estrus expression at TAI, sire, and month of parturition are important factors influencing P/AI and rates of embryonic mortality in beef herds.